PENGENALAN POTENSI WISATA DAN POTENSI UNGGULAN DESA TELUK MELALUI PEMBUATAN VIDEO PROFIL DESA - Vadilla Mutia Zahara (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Teluk village, which is comprised mostly of pandeglang Regency of Banten, is full of tourist potential and plenty of potential fishing sectors. But that potential is still largely unknown to the general public. In order for that potential to grow and increase market-value or value-added so as to impact community and local economies, it is vital that an area promote its territory. One of the efforts was to create a village profile video that was uploaded on some social media like youtube. Teluk village profile video is an outlet for the implementation of the thematic untirta group 82 KKM, made with the purpose of introducing the presence and potential of the gulf village, using a virtual ethnographic approach where this method is used to look at social media phenomenon, and it uses qualitative data analysis methods to draw conclusions from observations, interviews, surveys, field observations, Which is used in promoting and introducing Teluk village potential with a preproduction/production/post video-production. Of the 30 respondents and communities who watch village profiles, there is a positive response from the user or people who watch these profiles include some positive comments and expressions of people's desire to get to know and visit Teluk village, and there are several regional improvement recommendations and hopes for developing infrastructure, development and governance from various aspects of Teluk village, It is hoped that the video will enable Teluk village to unveil and increase the added value of tourist potential and a preening potential for Teluk Labuan Village.